The Role of ESG and External Assurance in Firm Performance: External Assurance as a Moderator - Eduard Ary Binsar Naibaho; Dara Raudhotuzanah (JASF: Journal of Accounting and Strategic Finance, 2025)
Purpose: This study seeks to assess the impact of Environmental, Social, and Governance (ESG) factors and External Assurance on Firm Performance, with External Assurance acting as a moderating variable in the ESG-Firm Performance relationship. This research is based on agency theory, which explains the potential conflict of interest between management and shareholders over sustainability spending. Method: This research employs a quantitative methodology, utilizing panel data regression analysis. The sample consists of 120 publicly listed non-financial companies from ASEAN-5 countries over the period 2019–2023. Secondary data were obtained through a literature review from S&P Capital IQ and Thomson Reuters Eikon, and the sample was selected using a purposive sampling technique. Findings: The study’s results indicate that ESG and External Assurance have a negative impact on Company Performance, as indicated by Tobin’s Q, with coefficient values of -0.013 and -0.214. However, neither does it show a significant influence when measured by ROA. Furthermore, External Assurance influences the relationship between ESG and Company Performance (Tobin’s Q) with a coefficient value of -0.002. Still, it does not affect the relationship when ROA is used as a measure of Firm Performance. Novelty/Value: This study contributes to the current literature by providing empirical evidence on the moderating effect of External Assurance on the relationship between ESG and Firm Performance within the ASEAN-5 countries, incorporating two performance metrics.